2013
DOI: 10.5539/jas.v5n10p273
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Awareness in Mpumalanga Province, South Africa

Abstract: Climate change is one of the most important environmental issues facing the world today. The impact of climate change is a reality and it cuts across all climate-sensitive sectors including the Agriculture sector. It is well documented by several scientists, Intergovernmental Panel on Climate Change and other experts that climate change threatens sustainable economic development and the totality of human existence. This study will enable small scale maize farmers in Mpumalanga province to understand the challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
4
15
0
Order By: Relevance
“…From statistics in the Mekong Delta, tourism authorities have highest evaluation of climate change impacts, followed by businesses and domestic tourists. This finding is in line with the findings from Maponya, Mpandeli, and Oduniyi (2013) and Nzeadibe, Egbule, Chukwuone, and Agu (2011) that availability of information and level of education would decide ones evaluation on an issue. In this study, tourism authorities who have access to more information on the climate-tourism relation, as well as higher quality knowledge, and are experts in the field tend to have a negative outlook of the impact of climate change on regional tourism.…”
Section: Another Surprising Finding Fromsupporting
confidence: 90%
“…From statistics in the Mekong Delta, tourism authorities have highest evaluation of climate change impacts, followed by businesses and domestic tourists. This finding is in line with the findings from Maponya, Mpandeli, and Oduniyi (2013) and Nzeadibe, Egbule, Chukwuone, and Agu (2011) that availability of information and level of education would decide ones evaluation on an issue. In this study, tourism authorities who have access to more information on the climate-tourism relation, as well as higher quality knowledge, and are experts in the field tend to have a negative outlook of the impact of climate change on regional tourism.…”
Section: Another Surprising Finding Fromsupporting
confidence: 90%
“…A structured questionnaire was administered through the internet using Google forms. The questionnaire entailed close-ended questions which were drafted based on a review of questionnaires used by similar studies [6,7,9,46,47]. The link to the online questionnaire was administered through emails using a process similar to Salant and Dillman's [48] four-stage process for administering questionnaires by mail or post.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Watkins [5], for instance, argued that public perception can significantly influence future development and environmental policies. In this regard, public perceptions, awareness and knowledge of climate change have received increased attention in the literature in recent times [6][7][8][9][10][11][12][13][14][15]. It is argued that individual behaviour is central to climate change because individuals influence large procedures of change and policy decisions [16].…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in Table 1 and Table 2, the chi-square test supports the argument that there is no significant association between gender and qualification and extent to which participants know about climate change. Due to the differences in the method of sampling the population, this finding is different to the outcome of Buloshi and Ramadan (2015) and Maponya et al (2013) which identified that gender and qualification is important in climate awareness levels. This study has targeted specific group of respondents (tourism authorities and businesses) and relied on the convenience sample method while other studies targeted the whole population and rely on a randomly sample method.…”
Section: Climate Change Knowledge Of Stakeholders In Tourism Sector Imentioning
confidence: 86%
“…Climate change knowledge has been found to depend on various factors such as gender, ages, level of education, social status, income and availability of information (Buloshi & Ramadan, 2015;Mandleni & Anim, 2011;Maponya, Mpandeli, & Oduniyi, 2013;Nzeadibe et al, 2011;Odjugo, 2013). Nowadays, with the popularity of information technology and a variety of communication methods, the information is much quicker and easier to transfer between communities.…”
Section: Climate Change Knowledge Of Stakeholders In Tourism Sector Imentioning
confidence: 99%